Pelatihan dan Pendampingan Guru dalam Pengembangan Pembelajaran Deep Learning Terintegrasi Media Digital untuk Meningkatkan Literasi Digital di Sekolah Dasar - Intan Safiah; Aida Fitri; Martines Martines; Alief Nasyawal Achdar; Zaharatunnisa Zaharatunnisa (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The transformation of technology-based learning in elementary schools is an urgent need to improve educational quality and support the achievement of the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education) and Goal 10 (Reduced Inequalities). This study aims to enhance the competence of teachers at SD Negeri Perumnas Neuheun in developing deep learning-based instruction integrated with digital learning applications. The method employed was participatory action research through stages of socialization, intensive training, technology implementation, mentoring, evaluation, and sustainability strategies. Twenty teachers participated in the two-month program, which included the introduction of deep learning concepts, the use of digital applications (Quizizz, Google Classroom, Kahoot, GeoGebra, Canva), and the development of project-based learning digital modules. Results indicated a significant improvement in teacher competence: digital literacy scores increased from an average of 58.2 to 82.7; deep learning comprehension rose from 55.4 to 83.2; and blended learning skills improved by 41.89%. Moreover, 90% of teachers reported higher confidence in teaching with technology and demonstrated increased collaboration through a digital teacher community forum. In conclusion, this training and mentoring program effectively improved elementary school teachers’ competencies, fostered a digital learning culture, and can be replicated in other schools to support the SDGs agenda in education.